2017
DOI: 10.2174/1567205014666170117103217
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Model of Alzheimer's Disease: Aβ1-42 Peptide Induces Amyloid Deposition and a Decrease in Topo Isomerase IIβ and Nurr1 Expression

Abstract: Our findings suggest that topo IIβ could be a down-stream target of signaling pathways contributing to AD-like pathology. However, further studies must be carried out in vivo to elucidate the precise association topo IIβ with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Integrating data from human post-mortem brain studies, HSPA1A (Hsp70Aa ortholog) upregulates in the protein interaction network of AD patients compared to healthy controls 63 , and has recently been suggested to block APP processing and Aβ production in mouse brain 64 . Synthetic, fibrillar, Aβ42 reduces expression of TOP2B (Top2 ortholog) in rat cerebellar granule cells and in a human mesenchymal cell line, suggesting this may contribute to DNA damage in response to amyloid 65 . HSP90B1 (Gp93 ortholog) shows increased expression following TBI in mice 66 , and associates with animal models of Huntington’s disease 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrating data from human post-mortem brain studies, HSPA1A (Hsp70Aa ortholog) upregulates in the protein interaction network of AD patients compared to healthy controls 63 , and has recently been suggested to block APP processing and Aβ production in mouse brain 64 . Synthetic, fibrillar, Aβ42 reduces expression of TOP2B (Top2 ortholog) in rat cerebellar granule cells and in a human mesenchymal cell line, suggesting this may contribute to DNA damage in response to amyloid 65 . HSP90B1 (Gp93 ortholog) shows increased expression following TBI in mice 66 , and associates with animal models of Huntington’s disease 67 .…”
Section: Discussionmentioning
confidence: 99%
“…• Nurr1 immunofluorescence intensity is reduced in the substantia nigra of AD patients [13] • Nurr1 mRNA levels are reduced in APPswe, lnd mutant mice [62,63] • The number of Nurr1(+) cells is age-dependently reduced in the subiculum of 5XFAD mice [90] • Nurr1 protein is co-localization with Aβ at the early stage in 5XFAD mice [90] • Nurr1 protein and mRNA are downregulated in Aβ1-42 fibril-treated CGNs and the hMSC cell line [65] Neuroprotective effects…”
Section: References Nurr1 Expression In Admentioning
confidence: 99%
“…Interestingly, Nurr1 is known to act as a critical regulator of hippocampal function, hippocampal synaptic plasticity, and cognitive functions [15,[48][49][50][51][52][53][54][55], and is an essential mediator of neuroprotection or anti-inflammation after exposure to neuropathological stress [19,[56][57][58][59][60][61]. In addition, a number of studies have indicated altered levels of Nurr1 in Aβ-treated neuronal cells, animal models of AD, and the brains of patients with AD [13,[62][63][64][65], implying that Nurr1 may play a role in the pathogenesis of AD. Recent studies have shown that Aβ1-42 fibrils not only lead to upregulation of tau hyperphosphorylation and presenilin 1 mRNA, which are hallmarks of AD pathology, but also significantly reduce Nurr1 mRNA levels in an in vitro model of AD [65].…”
Section: The Roles Of Nurr1 In Ad-related Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of Topo IIβ in the maintenance of chromatin architecture and transcription also has important pathophysiological implications. On the one hand, alterations in Topo IIβ levels could affect the transcription of selective genes that govern neurite outgrowth and axonogenesis, and contribute to various neurological disorders [ 47 , 82 ]. On the other hand, the formation of DSBs in the promoters of stimulus-responsive genes during transcription induction suggests that changes in the ability to repair these stimulus-induced DSBs could have detrimental consequences ( Figure 2 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%